Fabrication of a flexible and conductive lyocell fabric decorated with graphene nanosheets as a stable electrode material. (5th November 2016) - Mengal, Naveed; Sahito, Iftikhar Ali; Arbab, Alvira Ayoub; Sun, Kyung Chul; Qadir, Muhammad Bilal; Memon, Anam Ali; Jeong, Sung Hoon
Highlights: A wearable, flexible and conductive lyocell fabric is produced. The fabric is coated with graphene nanosheets using simple dip and dry technique. The fabric is stable against the effect of electrolyte and bending. The surface resistance of the graphene coated lyocell fabric is only 40 Ω sq −1 . Abstract: Textile electrodes are highly desirable for wearable electronics as they offer light-weight, flexibility, cost effectiveness and ease of fabrication. Here, we propose the use of lyocell fabric as a flexible textile electrode because of its inherently super hydrophilic characteristics and increased moisture uptake. A highly concentrated colloidal solution of graphene oxide nanosheets (GONs) was coated on to lyocell fabric and was then reduced in to graphene nanosheets (GNs) using facile chemical reduction method. The proposed textile electrode has a very high surface conductivity with a very low value of surface resistance of only 40 Ω sq −1, importantly without use of any binding or adhesive material in the processing step. Atomic force spectroscopy (AFM) and Transmission electron microscopy (TEM) were conducted to study the topographical properties and sheet exfoliation of prepared GONs. The surface morphology, structural characterization and thermal stability of the fabricated textile electrode were studied by field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FT-IR), X ray photon spectroscopy (XPS), Raman spectroscopy, Wide angle X ray diffraction spectroscopy (WAXD) and Thermogravimetric analysis (TGA) respectively. These results suggest that the GONs is effectively adhered on to the lyocell fabric and the conversion of GONs in to GNs by chemical reduction has no adverse effect on the crystalline structure of textile substrate. The prepared graphene coated conductive lyocell fabric was found stable in water and electrolyte solution and it maintained nearly same surface electrical conductivity at various bending angles. The electrical resistance results suggest that this lyocell based textile electrode (L-GNs) is a promising candidate for flexible and wearable electronics and energy harvesting devices.